A reflection of the intellectual achievement of Professor Direk Jayanama in his personal book collection donated to the Thammasat University Library - Ivry, Benjamin; Laorukwong, Arocha (วารสารวิชาการหอสมุดแห่งชาติ, 2025)
The aim of this article is to make international researchers more aware of resources that clarify the literary inspiration of Direk Jayanama, a key figure in Thai history. This is reflected through his personal library, which consists of 382 volumes on history, political science, diplomacy, spirituality, ethics, and literature. Students and instructors may benefit from these books which constitute an intellectual portrait of the human ideals that may have inspired Direk’ s accomplishments as a public servant and statesman. To add to a general understanding of the intellectual motives and achievements of one of the distinguished participants in modern Thai history, future research on Direk Janayama and his work might consider this documentation now available for scholarly investigation at the Faculty of Political Science, Thammasat University Library. Challenges to preserving and maintaining this collection, as well as a road map for future maximum public benefit, are presented.